A bibliometric analysis of atezolizumab in hepatocellular carcinoma - Yuqing Xu; Hucheng Zhang; Haipeng Yu (Discover Oncology, 2025)
Abstract Background Hepatocellular carcinoma (HCC) is a highly prevalent primary liver cancer, accounting for over 90% of all liver cancer cases worldwide and ranking as the third leading cause of cancer-related deaths. The emergence of molecular targeted therapies has completely transformed the treatment landscape for HCC. Among them, sorafenib, as the first molecular targeted drug approved by the FDA, established a treatment standard that lasted for over a decade. However, recent research breakthroughs have shown that the combination therapy of atezolizumab and bevacizumab demonstrates superior efficacy compared to sorafenib, and this combination was approved by the FDA in 2020. Numerous studies have been published on the treatment of hepatocellular carcinoma with atezolizumab; however, no bibliometric study has been published. The aim of this study is to better understand the current situation and identify potential new research directions by conducting a bibliometric analysis on the treatment of hepatocellular carcinoma with atezolizumab. Methods We searched the Web of Science Core Collection (WoSCC) for articles related to the treatment with Atezolizumab for HCC. Two software (VOSviewer and CiteSpace) were primarily used to assess the contribution and co-occurrence relationships of various countries/regions, institutes, journals, and authors. They were also employed to identify the research hotspots and potential development trends in this research field. Objective To understand the development status and future trends of atezolizumab in the treatment of hepatocellular carcinoma, we used bibliometric analysis to investigate the cooperation and influence among countries, institutions, authors and journals. Results A total of 1067 articles published by 6318 authors from 1747 institutions in 254 journals from 2016 to 2024 were retrieved. A rapid increase in articles published after 2020 was observed and peaked in 2023. China has the largest number of publications and citations. ASSISTANCE PUBLIQUE HOPITAUX PARIS (APHP), NATIONAL TAIWAN UNIVERSITY, and UNIVERSITE PARIS CITE(n = 92, 8.62%) are the three leading institutions for research on this topic. KUDO M and FINN RS have had the greatest academic influence in this area. Most of the publications were published in the journal CANCERS, while the most cited journal was j hepatol. The main aspects of atezolizumab in the treatment of hepatocellular carcinoma include immunotherapy, hepatocellular carcinoma, research methods, survival prognosis, and targeted therapy. Hepatocellular carcinoma, sorafenib, atezolizumab, atezolizumab plus bevacizumab, bevacizumab, immunotherapy and other keywords are hot words in this field in recent years. Conclusion Atezolizumab has become an increasingly popular treatment for hepatocellular carcinoma. Future studies should focus on the efficacy of atezolizumab plus bevacizumab and TACE-HAIC combination therapy in patients with HCC.